Students-athletes accompaniment program: A succesful expirience at the Santo Tomas University (Impetus, 2021)
Sport is synonymous of perseverance, discipline, personal and collective overcoming; it helps to promote the acceptance of the other, and allows to enhance affective, psico-social and physical aspects. Colombia is being internationally- recognized as a nation that is positioning itself in several sports discipline progressively, and this situation has produced some social transformations that have helped to the nation’s development process. Paradoxically, when an athlete is looking for entrance into university in order to become a professionally competitive person in the future, in the majority of the cases has to make a decision: to stay at the university and leaves the sport, or staying in his/her discipline sport and leaving his/her university studies. The Faculty of Physical Culture, Sport and Recreation of the Santo Tomas University has understood this situation and it has decided to promote, to forge and to implement an Athlete-Student Accompaniment Program which will enable to harmonize the sporting commitments with academic responsibilities. It has been of this way because this support process understood that the comprehensive training of a person entails inclusion and exaltation of every detail that helps him/her to be valious as a human being, over the simply academic-process. This article describes both program fundamentals and guidelines, as well as achievments and perspectives either; that’s how the program has becoming a succesful process into the Faculty.